Candidate Molecules that Alter the Abnormal Mucosal Immune System in Human Type 1 Diabetes - Outi Vaarala (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
The link between the gut immune system and type 1 diabetes (T1D) has been suggested by studies which have demonstrated that dietary factors modify the disease in animal models of autoimmune diabetes. In humans, some studies suggest that autoreactive T-cells may originate from the gut immune system. For example, T-cells derived from pancreas of a patient with type 1 diabetes adhered to mucosal and pancreatic endothelium. Also autoreactive T-cells from patients with T1D expressed the gut-associated homing receptor, alpha4beta7-integrin. When intestinal biopsy samples from children with T1D but without signs of celiac disease were studied, markers of inflammation are up-regulated. Intestinal immune activation is seen as increased expression of HLA class II molecule and ICAM-1 throughout the epithelial cells. The densities of IL-4 and IL-1alpha positive cells are increased in the lamina propria. Intestinal biopsy samples from patients with T1D show aberrant reaction of immune activation seen as expansion of CD3 and CD25 cells when stimulated with wheat gliadin in vitro. This suggests that wheat gliadin could be a trigger of intestinal inflammation not associated with celiac disease but present in children with T1D. Another dietary candidate for the trigger of intestinal inflammation in T1D is dietary insulin present in cow milk, a dietary risk factor linked to T1D. Enterovirus and rotavirus infections associated with the risk of beta-cell autoimmunity are known to change the permeability of the gut as well as cytokine environment and could stimulate the intestinal immune system by these mechanisms. The composition of intestinal microflora is important for the development of balance between tolerance and immunity in the gut immune system. The changes in the intestinal microflora are discussed as a cause of sub-clinical intestinal inflammation associated with T1D. The gut hypothesis suggests that the underlying sub-clinical intestinal inflammation allows the development of destructive beta-cell autoimmunity in genetically susceptible individuals who are not able to control the immune response to dietary antigens such as insulin due to interference of environmental factors which break oral tolerance.
Keywords: DQ8 alleles